A genome‑wide association study identifying the SNPs predictive of rapid joint destruction in patients with rheumatoid arthritis. Issue 3 (18th December 2020) - HAYASHI, SHINYA; MATSUBARA, TSUKASA; FUKUDA, KOJI; MAEDA, TOSHIHISA; FUNAHASHI, KEIKO; HASHIMOTO, MAROWA; KAMENAGA, TOMOYUKI; TAKASHIMA, YOSHINORI; KURODA, RYOSUKE
No abstract available